(untitled) (Bangladesh Journal of Otorhinolaryngology, 2025)
Introduction: Thyroidectomy is a preferred operation for various thyroid disorders in vasion forms and extent. Postoperative hypocalcaemia and hypoparathyroidism are the common complications. So measuring calcium and PTH level pre and postoperatively is important in planning management of thyroid disease. It can predict the risk of a surgery. Aim of the study: The Aim of the study is to compare serum calcium and parathyroid hormone levels in preoperative and postoperative studies. Methods: A prospective observational study was conducted in the Head and Neck Surgery Division of the Department of Otolaryngology-Head & Neck Surgery, BSMMU, Shahbag, Dhaka from August 2022 to January 2023. 35 patients underwent parathyroidectomy. The data was collected and analyzed using SPSS 26.0 (Statistical Package for the Social Science). The statistical significance was set to p<0.05. Result: In this series, the majority of the patients (19, 54.29%) were in the 58 to 68 years age group. Among them, the majority (71.0%) of the patients were female. It was observed that the majority (54%) of the study subjects were symptomatic and 46% of the patients were asymptomatic. Here, 3(8.5%), 6(17.1%), and 2 (5.7%) patients presented with osteitis fibrosa cystica, nephrolithiasis, and neuropsychiatric syndrome respectively. Moreover, 14(40.0%) patients had muscle weakness, and 18 (51.0%) subjects presented with fatigue. In this study, parathyroid adenoma was found in 85.75% and 74.90% of patients in symptomatic and asymptomatic patients respectively. Preoperative PTH and calcium levels, and postoperative calcium levels in SPHPT and ASPHPT were found statistically significant. Conclusion: This study provides evidence supporting the enduring advantages of parathyroidectomy in individuals with primary hyperparathyroidism (PHPT). The observed reduction in pre-operative symptoms seems to be a significant factor contributing to the enhanced quality of life (QOL) experienced by these patients over the long term. Bangladesh J Otorhinolaryngology 2025; 31 (1) Page-35-46